P–048 Effects of bisphenol S and bisphenol F on human spermatozoa: an in vitro study. (6th August 2021) - Castellini, C; Giammarco, N D; D'Andrea, S; Parisi, A; Totaro, M; Francavilla, S; Francavilla, F; Barbonetti, A
Abstract: Study question: Are plasticizers bisphenol S (BPS) and bisphenol F (BPF) safer alternatives to bisphenol A (BPA) for human sperm function? Summary answer: Unlike BPA, the analogues BPS and BPF do not significantly affect human sperm mitochondrial functions, motility and viability What is known already: The widespread distribution of BPA, along with its reputation to be an endocrine disruptor has generated concerns about possible adverse effects for human health, thus prompting the European Food Safety Authority and the Food and Drug Administration to ban the use of this chemical in many plastic products. Following such restrictions, several substitutes have been developed, with BPS and BPF representing the main replacements to BPA. While it has been demonstrated that BPA promotes oxidative damages in spermatozoa from different species, including human, the possible effects exerted by BPS and BPF on human sperm, have not yet been investigated. Study design, size, duration: We explored the effect of 4 h in vitro exposure to scalar concentrations of BPS and BPF (from 10 to 400 μM), and to 400 μM BPA on sperm motility, viability, mitochondrial membrane potential (Δm) and mitochondrial generation of reactive oxygen species (ROS). In a set of experiments, the effect of a combination of both BPF (400 μM) and BPS (400 μM) on ΔΨm and mitochondrial ROS generation was also assessed. Participants/materials, setting, methods: Sperm Δm was analyzed by flow cytometry with the fluorescent lipophilic cationic dye JC–1. Flow cytometric assessment of mitochondrial generation of ROS was carried out using the lipid soluble cation MitoSOX red (MSR). Sperm motility and viability were evaluated by Computer-Aided Semen Analysis (CASA) and eosin assay, respectively. Main results and the role of chance: The exposure to scalar concentration of BPS did not significantly affect sperm motility and viability with respect to untreated controls. A lower, albeit not significant, sperm motility was registered in samples exposed to the highest concentrations of BPF (300 μM and 400 μM). As expected, 400 μM BPA produced a complete sperm immobilization along with a dramatically loss in sperm viability. No significant differences were observed in sperm Δm and ROS generation after exposure to scalar concentration of BPS compared to untreated controls and the trend towards lower Δm and higher mitochondrial ROS generation at the highest concentrations of BPF did not reach statistical significance. On the contrary, after 4 h exposure to 400 μM BPA a significant lower Δm and higher mitochondrial ROS generation were observed. Finally, the exposure to a combination of BPF and BPS at high concentrations (400 μM) did not significantly affect sperm Δm, or mitochondrial ROS generation, when compared to 400 μM BPA, used as positive control. Limitations, reasons for caution: The present study only evaluated BPS and BPF effects, but in daily-life people are exposed to several plasticizers containing different bisphenols at different concentrations. Therefore, adverse effects of synergic exposure to BPA analogues other than BPS and BPF, alone or in combination with BPA, cannot be ruled out. Wider implications of the findings: The analogues BPS and BPF, alone or in combination, appeared to be safer alternatives to BPA on sperm biology as they exert a neutral effect on sperm motility, viability, and mitochondrial functions even at high concentrations. These results could be useful to identify more secure plasticizer components. Trial registration number: Not applicable